IMPLEMENTASI GERAKAN LAUDATO SI’ MELALUI KEGIATAN ECO-ENZYME SEBAGAI BENTUK PERTOBATAN EKOLOGIS UMAT PAROKI SANTO YOHANES RASUL PRINGWULUNG YOGYAKARTA - Wullo, Maria Hubertina Sa; Wono Wulung, F.X. Heryatno (CREDENDUM: Jurnal Pendidikan Agama, 2025)
The purpose of this study is to examine the extent to which the parish community implements the Laudato Si’ movement through eco-enzyme activities as a form of ecological conversion, and to identify the supporting and inhibiting factors in its implementation. Laudato Si’ is an encyclical that calls on humanity to care for our common home, grounded in both moral and scientific reasoning. In response, the parishioners of Pringwulung have adopted eco-enzyme practicesan environmentally friendly method of processing organic waste into beneficial productsas a concrete effort to live out ecological values. This qualitative field research employed methods such as active observation, in-depth interviews, and focus group discussions (FGDs). The findings reveal that the parishioners are actively engaged and committed to implementing the Laudato Si’ movement through eco-enzyme practices. This is demonstrated by their consistent and effective participation. The study concludes that the people of Pringwulung Parish are striving to embody the spirit of ecological conversion in their daily lives through the simple yet meaningful act of transforming fruit and vegetable waste into eco-enzyme products.